The Effect of the Cooperative Learning Model Assisted by Napkin AI Media on Islamic Religious Education Learning Outcomes of Fifth-Grade Elementary School Students - Nur Andini Rusli; Mujahidah; Sitti Rahmi (PT. Lontara Digitech Indonesia, 2026)
Islamic Religious Education (PAI) learning in elementary schools still faces various challenges, particularly the low learning outcomes of students due to the use of conventional learning methods and the lack of utilization of interactive digital learning media. This study aims to determine the effect of the implementation of the cooperative learning model assisted by Napkin AI media on the PAI learning outcomes of fifth-grade students at SDN 03 Balangnipa, North Sinjai District, Sinjai Regency. This study uses a quantitative approach with an experimental research type. The research subjects were all fifth-grade students of SDN 03 Balangnipa in the 2025/2026 academic year, totaling 25 students. The data collection technique used a learning outcomes test in the form of multiple-choice questions given before (pretest) and after (posttest) the implementation of the learning model. The data were analyzed using the Paired Sample t-Test. The results of the study showed that the average score of students’ learning outcomes before the treatment was 50.96, which was in the low category, while after the implementation of the cooperative learning model assisted by Napkin AI media, it increased to 81.80 and was in the high category. The results of the statistical test showed a significance value of 0.000 < 0.05, indicating a significant effect on students’ PAI learning outcomes. Thus, it can be concluded that the implementation of the cooperative learning model assisted by Napkin AI media is effective in improving the Islamic Religious Education learning outcomes of elementary school students.